2001
DOI: 10.1104/pp.126.2.789
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Expression Profile Analysis of the Arabidopsis Hsp70 Gene Family

Abstract: We isolated cDNA clones for two nuclear-encoded, organellar members of the Arabidopsis hsp70 gene family, mtHsc70-2 (AF217458) and cpHsc70-2 (AF217459). Together with the completion of the genome sequence, the hsp70 family in Arabidopsis consists of 14 members unequally distributed among the five chromosomes. To establish detailed expression data of this gene family, a comprehensive reverse transcriptase-polymerase chain reaction analysis for 11 hsp70s was conducted including analysis of organ-specific and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
379
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(403 citation statements)
references
References 48 publications
19
379
2
3
Order By: Relevance
“…PCC6803. This result was also in agreement with previous phylogenic analyses of HSP70 in yeast, plants, and other organisms [4,5,33,37], and suggested that TaHSC70 was a homolog of chloroplast HSP70s with prokaryotic origin.…”
Section: Discussionsupporting
confidence: 92%
“…PCC6803. This result was also in agreement with previous phylogenic analyses of HSP70 in yeast, plants, and other organisms [4,5,33,37], and suggested that TaHSC70 was a homolog of chloroplast HSP70s with prokaryotic origin.…”
Section: Discussionsupporting
confidence: 92%
“…Heat shock proteins perform a variety of functions in plants from protein folding to assembly, translocation, and degradation in cellular processes and can assist in the refolding of proteins under stress conditions. It has been demonstrated in expression profile studies that HSP70 genes are expressed in response to stresses such as heat, cold, drought, chemical, and other environmental stresses in Arabidopsis and spinach (Guy and Li 1998;Lin et al 2001;Sung et al 2001;Wang et al 2004). …”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…The HSP70 gene family in Arabidopsis (Arabidopsis thaliana) comprises 14 members, of which five are predicted to be cytosolic (Sung et al, 2001). Since plant RNA viruses replicate in the cytoplasm, we studied these five members for their induction by a range of compatible viruses.…”
Section: Induction Of Hsp70 In Arabidopsismentioning
confidence: 99%